Optimum MV Feeder Routing and Substation siting and rating in Distribution Network - Hasan, Ihsan Jabbar; Ab Ghani, Mohd Ruddin; Gan, Chin Kim (2014)
A distribution network planning consists of several complexity aspects due to the multiple decision variables. The main objective of the distribution system planning is to find the optimum number of substation, location, size and feeders routing. This paper proposes an evolutionary algorithm to determine the optimum distribution substation placement and sizing by using the particle swarm optimization algorithm and optimum feeder routing using modified minimum spanning tree algorithm. The proposed algorithm evaluates on the distribution network case with 164 load blocks. The results showed the effectiveness of the proposed algorithm to find the acceptable location and sizing of distribution substations with a proper routing of the feeder.